Post-HTS case report and structural alert: Promiscuous 4-aroyl-1, 5-disubstituted-3-hydroxy-2H-pyrrol-2-one actives verified by ALARM NMR. Issue 21 (1st November 2015) - Dahlin, Jayme L.; Nissink, J. Willem M.; Francis, Subhashree; Strasser, Jessica M.; John, Kristen; Zhang, Zhiguo; Walters, Michael A.
Graphical abstract: Abstract: Despite its wide use, not every high-throughput screen (HTS) yields chemical matter suitable for drug development campaigns, and seldom are 'go/no-go' decisions in drug discovery described in detail. This case report describes the follow-up of a 4-aroyl-1, 5-disubstituted-3-hydroxy-2 H -pyrrol-2-one active from a cell-free HTS to identify small-molecule inhibitors of Rtt109-catalyzed histone acetylation. While this compound and structural analogs inhibited Rtt109-catalyzed histone acetylation in vitro, further work on this series was halted after several risk mitigation strategies were performed. Compounds with this chemotype had a poor structure–activity relationship, exhibited poor selectivity among other histone acetyltransferases, and tested positive in a β-lactamase counter-screen for chemical aggregates. Furthermore, ALARM NMR demonstrated compounds with this chemotype grossly perturbed the conformation of the La protein. In retrospect, this chemotype was flagged as a 'frequent hitter' in an analysis of a large corporate screening deck, yet similar compounds have been published as screening actives or chemical probes versus unrelated biological targets. This report—including the decision-making process behind the 'no-go' decision—should be informative for groups engaged in post-HTS triage and highlight the importance of considering physicochemical properties in early drug discovery.